If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 3)(3x + -2) = 6 Reorder the terms: (3 + 2x)(3x + -2) = 6 Reorder the terms: (3 + 2x)(-2 + 3x) = 6 Multiply (3 + 2x) * (-2 + 3x) (3(-2 + 3x) + 2x * (-2 + 3x)) = 6 ((-2 * 3 + 3x * 3) + 2x * (-2 + 3x)) = 6 ((-6 + 9x) + 2x * (-2 + 3x)) = 6 (-6 + 9x + (-2 * 2x + 3x * 2x)) = 6 (-6 + 9x + (-4x + 6x2)) = 6 Combine like terms: 9x + -4x = 5x (-6 + 5x + 6x2) = 6 Solving -6 + 5x + 6x2 = 6 Solving for variable 'x'. Reorder the terms: -6 + -6 + 5x + 6x2 = 6 + -6 Combine like terms: -6 + -6 = -12 -12 + 5x + 6x2 = 6 + -6 Combine like terms: 6 + -6 = 0 -12 + 5x + 6x2 = 0 Begin completing the square. Divide all terms by 6 the coefficient of the squared term: Divide each side by '6'. -2 + 0.8333333333x + x2 = 0 Move the constant term to the right: Add '2' to each side of the equation. -2 + 0.8333333333x + 2 + x2 = 0 + 2 Reorder the terms: -2 + 2 + 0.8333333333x + x2 = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 0.8333333333x + x2 = 0 + 2 0.8333333333x + x2 = 0 + 2 Combine like terms: 0 + 2 = 2 0.8333333333x + x2 = 2 The x term is 0.8333333333x. Take half its coefficient (0.4166666667). Square it (0.1736111111) and add it to both sides. Add '0.1736111111' to each side of the equation. 0.8333333333x + 0.1736111111 + x2 = 2 + 0.1736111111 Reorder the terms: 0.1736111111 + 0.8333333333x + x2 = 2 + 0.1736111111 Combine like terms: 2 + 0.1736111111 = 2.1736111111 0.1736111111 + 0.8333333333x + x2 = 2.1736111111 Factor a perfect square on the left side: (x + 0.4166666667)(x + 0.4166666667) = 2.1736111111 Calculate the square root of the right side: 1.474317168 Break this problem into two subproblems by setting (x + 0.4166666667) equal to 1.474317168 and -1.474317168.Subproblem 1
x + 0.4166666667 = 1.474317168 Simplifying x + 0.4166666667 = 1.474317168 Reorder the terms: 0.4166666667 + x = 1.474317168 Solving 0.4166666667 + x = 1.474317168 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.4166666667' to each side of the equation. 0.4166666667 + -0.4166666667 + x = 1.474317168 + -0.4166666667 Combine like terms: 0.4166666667 + -0.4166666667 = 0.0000000000 0.0000000000 + x = 1.474317168 + -0.4166666667 x = 1.474317168 + -0.4166666667 Combine like terms: 1.474317168 + -0.4166666667 = 1.0576505013 x = 1.0576505013 Simplifying x = 1.0576505013Subproblem 2
x + 0.4166666667 = -1.474317168 Simplifying x + 0.4166666667 = -1.474317168 Reorder the terms: 0.4166666667 + x = -1.474317168 Solving 0.4166666667 + x = -1.474317168 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.4166666667' to each side of the equation. 0.4166666667 + -0.4166666667 + x = -1.474317168 + -0.4166666667 Combine like terms: 0.4166666667 + -0.4166666667 = 0.0000000000 0.0000000000 + x = -1.474317168 + -0.4166666667 x = -1.474317168 + -0.4166666667 Combine like terms: -1.474317168 + -0.4166666667 = -1.8909838347 x = -1.8909838347 Simplifying x = -1.8909838347Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.0576505013, -1.8909838347}
| 0=-16t^2+74 | | 12x-51=3 | | 11(y-6)+5(y-7)= | | Ln(3x-1)=1.6 | | 10x=22783 | | Y+5x=23 | | Zy-3=10 | | 6-3(6+2x)=0 | | 0=-16t^2+245 | | 7(y-8)=9y-56 | | 10+5(2-2x)=0 | | h=245+16x^2 | | 245=-16t^2+h | | y=(2y)+15 | | 7x+21x-8=7(4x+9) | | (y^2+4y+4)(y+2)= | | 2x^3=129 | | 8m-7=5m+11 | | z(t)=120(1/2)^t/32760 | | -16t^2-h+245=0 | | 6=1-3z | | 4x+x^2-25=2304 | | 19x-3=21X-5 | | 5x+19x-7=6(4x+3) | | 14x-118=62+5x | | h=-16t^2-11t+120 | | 2x-187=72-5x | | 2x-(x-1)=5(x-3) | | 42x^2-5x-3=0 | | -20=2(w+7)-4w | | t/25=14/10 | | -9x-73=67-14x |